2012
DOI: 10.1371/journal.pone.0032746
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin Derivative Ameliorates High Fat Diet-Induced Renal Failure in Diabetes

Abstract: Diabetic nephropathy is a serious complication of longstanding diabetes and its pathogenesis remains unclear. Oxidative stress may play a critical role in the pathogenesis and progression of diabetic nephropathy. Our previous studies have demonstrated that polyunsaturated fatty acids (PUFA) induce peroxynitrite generation in primary human kidney mesangial cells and heat shock protein 90β1 (hsp90β1) is indispensable for the PUFA action. Here we investigated the effects of high fat diet (HFD) on kidney function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 59 publications
2
21
0
2
Order By: Relevance
“…Of note, DMAG treatment attenuated the structural pathologic changes in the diabetic kidney, including glomerular hyperplasia and mesangial matrix expansion, as well as tubular atrophy, interstitial fibrosis, and inflammation, hallmarks of end-stage renal failure. In line with the recently reported effect of HSP90 inhibitor on high-fat diet-induced renal failure in diabetes (20), our work adds differences in treatment dose and duration and study samples and provides mechanistic details about the renoprotective action of DMAG in diabetic mice.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Of note, DMAG treatment attenuated the structural pathologic changes in the diabetic kidney, including glomerular hyperplasia and mesangial matrix expansion, as well as tubular atrophy, interstitial fibrosis, and inflammation, hallmarks of end-stage renal failure. In line with the recently reported effect of HSP90 inhibitor on high-fat diet-induced renal failure in diabetes (20), our work adds differences in treatment dose and duration and study samples and provides mechanistic details about the renoprotective action of DMAG in diabetic mice.…”
Section: Discussionsupporting
confidence: 67%
“…Preclinical data implicate HSP90 as a promising anti-inflammatory target in rheumatoid arthritis, systemic lupus erythematosus, uveitis, liver injury, and cardiovascular disease models (12,(15)(16)(17)(18). In diabetic animals, HSP90 inhibition improved insulin sensitivity (19), high-fat diet-induced renal failure (20), and neurodegeneration (21), but the underlying mechanisms involved in these antidiabetic actions are not well defined. Hence, in this work we investigate whether targeting HSP90 delays the progression of diabetes complications in a diabetes mouse model of concomitant renal and macrovascular disease.…”
mentioning
confidence: 99%
“…On a long term basis, tubulo-interstitial injury could be reflected by mitochondrial dysfunctions and increased expression of extracellular matrix proteins; the changes are similar to those seen in the glomerular compartment. In line with the observations that there is hyperlipidemia and high levels of non-esterified fatty acids in type 2 diabetes, Zhang et al (14) reported that a high fat diet induces glomerular as well as tubulo-interstitial damage in db/db mice, which could be alleviated by the inhibition of hsp90 accompanied with reduced levels of renal nitrotyrosine and mitochondrial Ca 2ϩ efflux. These observations suggest that various metabolic disturbances, whether related to hyperlipidemia or hyperglycemia, induce tubular damage and subsequent tubulo-interstitial injury, although this concept has been sparsely described in the literature.…”
mentioning
confidence: 64%
“…In summary, our study demonstrates that a prolonged intake of HFD, which is accompanied by disturbed glycaemic control (notably increased insulin resistance), can lead to measurable kidney damage (Boini et al 2010;Lee et al 2012;Zhang et al 2012). Treatment with R. groenlandicum, which improved insulin sensitivity in this diet-induced obesity model (Ouchfoun et al 2015), also improves parameters of kidney integrity.…”
Section: Discussionmentioning
confidence: 63%